Pelatihan Pengambangan Perangkat Pembelajaran IPA Terpadu Terintegrasi Al-Quran berbasis Blended Learning - Milya Sari; Adelia Alfama Zamista; Allan Asrar; Pipi Deswita; Irwin Syah Putra (Universitas Mathla'ul Anwar Banten, 2022)
TRAINING ON DEVELOPMENT OF AL-QURAN INTEGRATED SCIENCE LEARNING DEVICES BASED ON BLENDED LEARNING. One thing that the teacher must prepare before carrying out learning is learning tools. To prepare for this, teachers must always update their knowledge by referring to the needs of students and following technological developments. One of the needs of today's students is assistance to have good morals and technology-based learning because current students are students known as Generation Z. So that training is carried out on the development of integrated learning tools for integrated Al-Quran based on blended learning. The method used in this service activity is the method of training and technology substitution. The results of this activity showed that there was an increase in participants' knowledge about blended learning, how to integrate the Quran and science in learning, and an increase in the motivation of teachers in developing integrated science learning tools that integrated Al-Quran based on blended learning that could really be applied in learning activities.